Performing Ourselves Differently, Part 4 - Khan, Steven (Daily Express, 2008)
The final part of this article articulates the author's belief that a culture can only be dynamically transformed by performing itself differently. It asks the questions: "What if we take Holiness as an end for education?" and "What might it mean to perform Holiness as an educator?"
Keywords: Philosophy of education